(untitled) (Physical Education, Health and Social Sciences, 2026)
Pakistan’s construction sector, contributing 5.3% to GDP and driven by a cement industry with an installed capacity exceeding 86 million tons annually, faces mounting sustainability pressures from high energy consumption, coal dependency, substantial CO₂ emissions ( 8–10% of national total), and depletion of conventional aggregates. This review evaluates the incorporation of agricultural waste ashes rice husk ash (RHA), sugarcane bagasse ash (SCBA), wheat straw ash, corn cob ash, and cotton stalk ash as supplementary cementitious materials (SCMs) and partial fine aggregate replacements in concrete production. Pozzolanic reactivity, particularly of RHA and SCBA (SiO₂ content 70–90%, fineness 20–40 m²/g), enables 10–30% cement replacement while improving compressive strength (5–25% gain at 28–90 days), durability (reduced chloride permeability, sulfate resistance, water absorption), and workability when optimally processed (controlled burning at 600–700 °C, grinding to <45 μm). Life cycle assessment (LCA) studies indicate 15–40% reductions in global warming potential, fossil energy demand, and embodied carbon compared to ordinary Portland cement (OPC) concrete, alongside waste diversion from open burning (reducing 1.2–2.0 t CO₂-eq per ton of ash utilized). Field and lab trials in Punjab and Sindh demonstrate structural feasibility for non-load-bearing elements, pavements, and low-to-medium strength concrete (20–40 MPa), with cost savings of 8–20% from lower cement and disposal expenses. Challenges variable ash composition, seasonal supply, grinding energy, alkali-silica reaction risk, and limited standardization are addressed through preprocessing protocols, mix optimization, and policy recommendations (incentives for ash utilization, inclusion in building codes). Agricultural waste ash emerges as a regionally abundant, low-cost, circular solution to enhance sustainability and resilience in Pakistan’s rapidly urbanizing construction industry.